Praktik Suap di Birokrasi Pemerintahan Perspektif Tafsir Ahkam Al-Jinaiyyah - Marpaung, Zaid Alfauza; Yuslem, Nawir; Hamdani, Muhammad Faisal (JUNCTO: Jurnal Ilmiah Hukum, 2023)
The contemporary challenge faced by governmental bureaucracy revolves around the pervasive issue of corruption, particularly bribery. This research aims to scrutinize bribery practices within governmental bureaucracy through the lens of the tafsir ahkam al-jinaiyyah perspective, which is associated with the issue of bribery. The methodology employed is normative legal research with an Islamic legal concept approach, referencing the Quran and Hadith, subsequently analyzed qualitatively. Research findings indicate that bribery practices within the governmental bureaucracy, within the context of Islamic teachings, are considered acts of "risywah" used as a means of bribery to achieve specific objectives unlawfully. The tafsir ahkam al-jinaiyyah perspective explains that the act of "risywah" can be understood through the messages in the Quran, specifically in Surah Al-Baqarah verse 188 and Surah Al-Imran verse 161, as well as the teachings of the Prophet. From the perspective of tafsir ahkam al-jinaiyyah, these practices are categorized as attempts to seek wealth through illegitimate means and as treacherous actions for the recipients of bribes who have been entrusted with responsibilities in their positions. Allah SWT expressly prohibits these actions, whether as the giver, receiver, or intermediary of bribes. The prohibition against bribery, particularly concerning judges, is emphasized due to the frequent occurrence of bribery practices in legal decision-making.